Lactic acid bacteria isolated from the digestive tract of spiny lobsters (Panulirus homarus) and their potency as probiotics - FATURRAHMAN FATURRAHMAN; KIKI RIZKI AULIYAH; LARAS ALISHIA JUANDA; TRI WAHYU SETYANINGRUM; SARKONO SARKONO; BAMBANG FAJAR SURYADI; FARIQ AZHAR; BAYU PRIYAMBODO; WANDA QORIASMADILLAH (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Faturrahman, Auliyah KR, Juanda LA, Setyaningrum TW, Sarkono, Suryadi BF, Azhar F, Priyambodo B, Qoriasmadillah W. 2025. Lactic acid bacteria isolated from the digestive tract of spiny lobsters (Panulirus homarus) and their potency as probiotics. Biodiversitas 26: 1827-1835. Spiny lobsters (Panulirus homarus) are an on-demand marine fishery commodity with significant economic value. However, collected data indicate that the lobsters exhibit low growth rates and high mortality due to disease infection caused by Vibrio spp. The provision of probiotics in feed represents a potential solution to this issue. Lactic acid bacteria (LAB) have been identified as probiotics due to their ability to counteract pathogenic bacteria and synthesize enzymes capable of hydrolyzing complex molecules, such as proteins, carbohydrates, and lipids, thereby promoting organismal growth. The objective of this study was to isolate LAB from the digestive tract of spiny lobsters as probiotic candidates. The selection of LAB isolates from the digestive tract was based on their ability to inhibit the growth of Vibrio harveyi bacteria and their capacity to produce a range of extracellular enzymes, including proteases, lipases, and amylases. The results demonstrated the isolation of seven LAB isolates, classified as Pediococcus, Enterococcus, and Lactobacillus genera, which exhibited the capacity to impede the proliferation of V. harveyi. The majority of the isolated LAB were found to possess the ability to hydrolyze protein, starch, and fat, in addition to exerting inhibitory effects against the growth of V. harveyi. Among the isolates, SP6 exhibited the most promising characteristics as a probiotic candidate by demonstrating robust protein and fat hydrolysis abilities, along with a significant capacity to inhibit the growth of V. harveyi.